Prediction Of Two-Phase Relative Permeability In Porqus Media Based On Network Modeling Of Lattice Gas Automata - Dedy Kristanto; Mariyamni Awang (Scientific Contributions Oil and Gas, 2004)
The displacement of one fluid by another is controlled by the geometry of the pore space. The relative hydrodynamic conductance of each fluid at a given saturation is the relative permeability, while the pressure difference between the phases is the capillary pressure. These two functions determine the macroscopic fluid flow behavior in hydrocarbon reservoir over the scale of centimeters to kilometers.At the pore seale fluids reside in intergranular space of typical sedimentary rocks. The rock type and fluid properties are likely to change drastically through the reservoir, the only sample of rock come from drilling wells, which represents a tiny fraction of the total volume in a reservoir. Furthermore, relative permeability measurements on these samples are difficult and time consuming. To quantify and control uncertainty in recovery estimations, it is necessary to have some theoretical understanding of transport properties. Such understanding would enable us to predict the sensitivity of relative permeability to geological factors such rosity, and the nature of the fluids. This work is a pre- liminary step in this direction. A more important result from this work is that we are now able to quantify the change in the relative permeability to those geological factors.In this paper a pore structure and displacements mechanisms to model two-phase flow in porous media were constructed using lattice gas automata. The void space of the media is represented as a network of large spaces (pores) connected by narrower throats. The aggregation of cell pore volumes is used to calculate the porosity of the network and the fluid saturation when different cells are occupied by different fluids. By judicious choices for the distribution of pore and throat sizes of the network it is possible to predict relative permeability. For predicting the absolute and relative permeability, it is assumed that the viscous pressure drops occur across the throats.